STATE CHILDREN'S HEALTHCARE POLICY: ENFORCEABILITY, STRUCTURE AND SUBJECT MATTER - A.A. Baranov; Yu.E. Lapin (Вопросы современной педиатрии, 2007)
The article gives specific recommendations as to improve the enforceability of the children's rights for the healthcare. The authors suggest a law, pursuant to which to solve the enforceability issues of the children's rights for the health care shall be «the objective of the social and economic development of the Russian federation». They also give an advanced concept of the state children's healthcare policy. The researchers provide a scientific substantiation for the structure and subject matter of this concept in full compliance with the regulations of the convention on the rights of the child.Key words: children's health, state policy, convention on the rights of the child.